IMPLEMENTATION OF GEOGEBRA ONLINE BASED ON GUIDED INQUIRY TO INCREASE PROBLEM SOLVING ABILITY AND STUDENT LEARNING INDEPENDENCE - Windia Hadi; Ayu Faradillah (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Mathematical problem solving ability and student learning independence have a positive relationship and have an important role in learning, especially for students of mathematics education study program. Geogebra online is a learning medium to help students understand image visualization. Mathematical problem solving ability is the highest level among other mathematical abilities. This study aims to 1) test the improvement of students' mathematical problem solving skills using zoom with guided inquiry-based online geogebra better than students' mathematical problem-solving skills using zoom with guided inquiry without online geogebra, 2) examine the increase in student learning independence using zoom with online geogebra. guided inquiry based is better than student learning independence using zoom with guided inquiry without online geogebra. The method used is quantitative research with pretest posttest group design. Data analysis using the independent test, namely the t test. Before the t test, a prerequisite test was carried out first by testing the normality and homogeneity of the data. For learning independence questionnaire data, ordinal data was changed using Rasch model software into interval data and then data analysis using SPSS. DR. HAMKA odd semester 2021/2022 and the sample is two classes that were selected using purposive sampling technique. Data analysis used t test and normalized gain test to see the results of increasing problem solving abilities and learning independence. Based on the results of the research, it can be concluded that 1) The improvement of mathematical problem solving abilities of students who learn using zoom with guided inquiry-based online geogebra is better than students who use zoomed guided inquiry without online geogebra. The results of the increase in mathematical problem solving abilities of students in the online geogebra class based on guided inquiry obtained an increase in the high category and an increase in mathematical problem solving abilities students in the guided inquiry class without online geogebra obtained an increase in the medium category and 2) increased learning independence of students who learn using zoom with geogebra online guided inquiry based is better than students who use zoom with guided inquiry without online geogebra. The results of increasing student learning independence in the online geogebra class based on guided inquiry and guided inquiry class without online geogebra obtained an increase in the low category.Penelitian ini bertujuan untuk menguji peningkatan kemampuan pemecahan masalah matematis mahasiswa dan kemandirian belajar menggunakan zoom dengan geogebra online berbasis guided inquiry lebih baik daripada kemampuan pemecahan masalah matematis mahasiswa menggunakan zoom dengan guided inquiry tanpa geogebra online. Metode yang digunakan adalah penelitian kuantitatif dengan design pretes postes group design. Analisis data dengan menggunakan uji independent test yaitu uji t, Sebelum uji t dilakukan uji prasyarat terlebih dahulu dengan menguji normalitas dan homogenitas data. Untuk data angket kemandirian belajar data, ordinal diubah dengan menggunakan software research model menjadi data interval kemudian analisis data dengan menggunakan shops..Populasi penelitian ini adalah semua mahasiswa prodi pendidikan matematika Universitas Muhammadiyah Prof. DR. HAMKA semester ganjil tahun 2021/2022 dan sampel adalah dua kelas yang di pilih menggunakan teknik purposive sampling. Analisis data menggunakan uji t dan uji gain ternormalisasi untuk melihat hasil peningkatan kemampuan pemecahan masalah dan kemandirian belajar. Berdasarkan hasil penelitian di dapat bahwa Peningkatan kemampuan Pemecahan masalah matematis dan kemandirian belajar mahasiswa yang pembelajaran menggunakan zoom dengan geogebra online berbasis guidedinquiry lebih baik daripada mahasiswa yang menggunakan zoom dengan guided inquiry tanpa geogebra online. Hasil peningkatan kemampuan Pemecahan masalah matematis mahasiswa kelas geogebra online berbasis guided inquiry memperoleh peningkatan dalam kategori tinggi dan kelas guided inquiry tanpa geogebra online memperoleh peningkatan dalam kategori sedang. Hasil peningkatan kemandirian belajar mahasiswa kelas geogebra online berbasis guided inquiry dan kelas guided inquiry tanpa geogebra online memperoleh peningkatan dalam kategori rendah.